Hybrid State Engineering of Phase‐Change Metasurface for All‐Optical Cryptography. (13th October 2020) - Choi, Chulsoo; Mun, Sang‐Eun; Sung, Jangwoon; Choi, Kyunghee; Lee, Seung‐Yeol; Lee, Byoungho
Abstract: Chalcogenide material Ge2 Sb2 Te5 (GST) has bistable phases, the so‐called amorphous and crystalline phases that exhibit large refractive index contrast. It can be reversibly switched within a nanosecond time scale through applying thermal bias, especially optical or electrical pulse signals. Recently, GST has been exploited as an ingredient of all‐optical dynamic metasurfaces, thanks to its ultrafast and efficient switching functionality. However, most of these devices provide only two‐level switching functionality and this limitation hinders their application to diverse all‐optical systems. In this paper, the method to expand switching functionality of GST metasurfaces to three level through engineering thermo‐optically creatable hybrid state that is co‐existing state of amorphous and crystalline GST‐based meta‐atoms is proposed. Furthermore, the novel hologram technique is introduced for providing the visual information that is only recognizable in the hybrid state GST metasurface. Thanks to thermo‐optical complexity to make the hybrid state, the metasurface allows the realization of highly secured visual cryptography architecture without the complex optical setup. The phase‐change metasurface based on multi‐physical design has significant potential for applications such as all‐optical image encryption, security, and anti‐counterfeiting. Abstract : Here, the method to create the hybrid state Ge2 Sb2 Te5 metasurface is introduced and applied to all‐optical cryptography. Based on the optical–thermal analysis and hologram optimization process, the well‐protected visual text is included in the hybrid state metasurface. The all‐optical cryptography system dramatically improves security level while providing ultrafast operation speed without a complex optical setup.